Effects of Welfare Sanctions in Couple Households - Gerard J. van den Berg; Arne Uhlendorff; Markus Wolf; Joachim Wolff (Institute of Labor Economics (IZA), 2025)
Means-tested welfare benefits are usually provided at the household level. Job search effort of unemployed welfare benefit recipients is monitored, and non-compliance with job search requirements can lead to a sanction and therewith to a temporary drop in household income. Among unemployed couples on welfare, a sanction is typically induced by one of the partners but potentially the burden is shared by both. We consider effects of sanctions on their transition rates into work. We examine theoretical implications and provide empirical evidence based on administrative data from Germany. We find that sanctions increase the probability of entering employment for the sanctioned welfare recipient but also for their partner. Females react more strongly to a sanction of their partner than males.
Keywords: J64; J65; 330; unemployment; gender; monitoring; job search; social assistance; intra-household bargaining